Validation of ICD-9-CM codes for identification of acetaminophen-related emergency department visits in a large pediatric hospital - de Achaval Sofia; Feudtner Chris; Palla Shana; Suarez-Almazor Maria E (BMC, 2013)
Abstract Background Acetaminophen overdose is a major concern among the pediatric population. Our objective was to assess the validity of International Classification of Disease (ICD-9-CM) codes for identification of pediatric emergency department (ED) visits resulting from acetaminophen exposure or overdose. Methods We conducted a retrospective medical record review of ED visits at Texas Children's Hospital in Houston, Texas, between January 1, 2005, and December 31, 2010. Visits coded with 1 or more ICD-9 codes for poisoning (965, 977, and their subcodes and supplemental E-codes E850, E858, E935, E947, and E950 and their subcodes) were identified from an administrative database, and further review of the medical records was conducted to identify true cases of acetaminophen exposure or overdose. We then examined the sensitivity, positive predictive value, and percentage of false positives identified by various codes and code combinations to establish which codes most accurately identified acetaminophen exposure or overdose. Results Of 1,215 ED visits documented with 1 or more of the selected codes, 316 (26.0%) were a result of acetaminophen exposure or overdose. Sensitivity was highest (87.0%) for the combination of codes 965.4 (poisoning by aromatic analgesics, not elsewhere classified) and E950.0 (suicide and self-inflicted poisoning by analgesics, antipyretics, and antirheumatics), with a positive predictive value of 86.2%. Code 965.4 alone yielded a sensitivity of 85.1%, with a positive predictive value of 92.8%. Code performance varied among age groups and depending on the type of exposure (intentional or unintentional). Conclusion ICD-9 codes are useful for ascertaining which ED visits are a result of acetaminophen exposure or overdose within the pediatric population. However, because ICD-9 coding differs by age group and depending on the type of exposure, hypothesis-driven strategies must be utilized for each pediatric age group to avoid misclassification.